RANCANG BANGUN PENGGAJIAN KARYAWAN BERBASIS WEB PADA PT. SURGANYA MOTOR INDONESIA - Ria Wulandari; Aditya Giyantono; Agus Gunawan (UNIVERSITAS RAHARJA, 2017)
Computer is a tool to carry out activities in the field of administration or a place to store thousands of data that can be processed at any time without requiring a long time to do so.Payroll system is something that is very fundamental to the financial activities on a corporate or industrial establishments, because it affects the performance of the employee.Remuneration is a routine activity carried out for companies that are spending a relatively large company because it needed a good payroll system for the implementation of the payroll calculation until payment can be run efficiently and smoothly.So that in determining the salaries of the leaders should know about poduktifitas, office or class, length of work, and the work performance of each employee.Thus, the payroll system PT. Surganya Motor Indonesia must gain control and precise handling in the payment of salaries to prevent fraud and abuse. The method used in this research is the method of data collection including interviews, observation, and literature. The analytical methods used are the SWOT analysis, while the method of design using UML. The test method using black box method.The system is expected to reduce errors in the calculation of salary and can save time in the calculation of employees’ salaries. So as a facilitate a mechanism to solve a problem for those involved in the implementation of the payroll system employees at PT. Surganya Motor Indonesia.